Integrated shape memory alloy devices toward a high-performance glazed curtain wall seismic retrofit. (15th January 2019) - Casagrande, Lorenzo; Sisinni, Jessica; Bonati, Antonio; Occhiuzzi, Antonio; Auricchio, Ferdinando
Highlights: External façades influence locally and globally the strength of structures. Engineered Shape Memory Alloy devices are designed to provide dissipation. Locally, stresses in structural key members decrease equipping SMA-based façades. Globally, accelerations decrease and greater inter-storey drifts are allowed. Abstract: Recent dynamic events, such as Alaska and San Fernando earthquakes, have shown shortcomings in contemporary façade design processes, exacerbated by the occurrence of non-structural component damage and failure when subjected to extreme wind loads or seismic events. Accordingly, in the present work the feasibility of an original and advanced dissipation technology is pursued investigating on the façade performance by testing and modeling strategies. Initially, based on the experimental activities performed at the Construction Technologies Institute (ITC) laboratories of the Italian National Research Council (CNR), numerical simulations are run to interpret and reproduce the experimentally tested response of two full-scale façade units. Thereafter, sophisticated 3D finite element models are calibrated acquiring information on the fundamental mechanisms accountable for the dynamics in façades. Subsequently, by virtue of the peculiar properties of Shape Memory Alloys (SMA), such as superelasticity and shape memory effect, innovative curtain wall joints are designed, focusing on the improvement of the façade energy dissipation performance and on the enhancement of the overall structural behavior. Finally, the improvements are demonstrated both globally and locally: on one hand, traditional and novel curtain wall force-drift capacity curves are compared; on the other hand, the effectiveness of the suggested device is shown, when built on a reference structure.